1989
DOI: 10.1007/bf00441515
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy associated with ovarian tumour in a young girl: recovery after removal

Abstract: We report a 7-year-old girl who presented with membranous glomerulonephritis and steroid-resistant nephrotic syndrome in association with a benign ovarian tumour. Surgical excision of the tumor led to complete disappearance of the proteinuria within 2 weeks. Tumour-associated membranous nephropathy in children is rare, as a review of the literature shows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Membranous nephropathy associated with benign tumor have also been reported by several authors [2][3][4], but up to now, we have not found an association between membranous nephropathy and granuloma.…”
mentioning
confidence: 43%
“…Membranous nephropathy associated with benign tumor have also been reported by several authors [2][3][4], but up to now, we have not found an association between membranous nephropathy and granuloma.…”
mentioning
confidence: 43%
“…The possibility of a fortuitous association must be considered. However, the assumption of a cause-effect link between these two conditions is highly attractive, especially since our patient had improved her nephrotic syndrome after oophorectomy, as occurred in the case reported by Beauvais et al [14], but this patient's tumor was detected too late, and nephrotic syndrome did not revert. In addition, embryonal carcinoma is considered a manifestation of chronic antigenic stimulation due to production of fetal antigens [19]; it is also associated with an altered immune state, exhibiting a strong hyperimmune response to both endogenous or experimentally administered antigens [7].…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, only a few cases with ovary tumors associated with nephrotic syndrome have been reported. Reviewing the literature, we have found 5 cases (table 1) with glomerulonephritis and ovary tumors: 2 cases described by Lee et al [1], 2 cases reported by Torres and Donadio [9], and 1 case described by Beauvais et al [14]. MPGN is a morphological entity and is associated with chronic primary, and usually progressive, glomerulonephritis that occurs in older children and adults [9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remission of MN-related nephrotic syndrome by cancer resection (2,3,16,17), chemotherapy (18), or radiation therapy (19) has been reported. In the present case, the extent of urinary protein excretion and edema did not change after the first session of radiation therapy to the pelvis.…”
Section: Discussionmentioning
confidence: 99%